Law Enforcement Against Perpetrators of Criminal Acts of Child Abuse Committed by Parents - Walangadi, Nurahma M; Darmawati, Darmawati; Makkulawuzar, Kingdom (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze law enforcement against perpetrators of criminal acts of child abuse committed by parents, as well as to find out the factors that affect the law enforcement process. Cases of child abuse by parents are a form of serious violation of the rights of children who should receive protection, as stipulated in Law Number 35 of 2014 concerning Child Protection. The research method used is a normative juridical method with a legislative approach and case studies. Data was obtained through literature studies of laws and regulations, legal literature, and court decisions related to cases of child abuse by parents. The results of the study show that law enforcement against perpetrators of child abuse by parents still faces various obstacles, including cultural factors, lack of reporting from the public, and the consideration of law enforcement officials on the blood relationship between the perpetrator and the victim. Although the law has given strict sanctions to perpetrators of child abuse, in practice law enforcement is often compromising on the grounds of family interests. Therefore, it is necessary to increase public legal awareness, the professionalism of law enforcement officials, and the application of the principle of the best interest of the child in every stage of the legal process so that children's rights can be optimally protected.